Study the Effect of Depleted Uranium Used by Coalition Forces in Increasing of Cancer Disease in Diyala governorate (مجلة ديالى للبحوث الانسانية, 2022)
During the gulf war against Iraq the coalition forces used large amount depleted uranium DU .So this study aims to highlight the effects of DU on cancer disease in Diyala. The study shows that the direct or indirect exposure to depleted uranium DU cause an increasing in the rate of cancer disease in Diyala governorate specially in some kinds of cancer such as lung cancer, Leukemia and Breast cancer that show high level.